2017
DOI: 10.1007/s10103-017-2254-2
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation therapy action in wound repair skin induced in aged rats old: time course of biomarkers inflammatory and repair

Abstract: Previous studies have discussed an inverse correlation between age and wound healing, because it relates to the association of aging with a gradual decrease in healing capacity. Treatment with photobiomodulation therapy (PBMT) improves wound healing by inducing increases in mitotic activity, numbers of fibroblasts, collagen synthesis, and neovascularization. Therefore, this study aimed to evaluate the effects of PBMT in cutaneous wound healing in aged rats. A punch biopsy of 8 mm in diameter was performed to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 35 publications
0
12
0
2
Order By: Relevance
“…The induction of skin lesions using a 6-mm skin punch was performed successfully in all animals and helped standardize lesions of similar sizes in the experimental animals, similarly to techniques reported in previous studies (KAWALEC et al, 2004;PEREIRA et al, 2010;FIORIO et al, 2017).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The induction of skin lesions using a 6-mm skin punch was performed successfully in all animals and helped standardize lesions of similar sizes in the experimental animals, similarly to techniques reported in previous studies (KAWALEC et al, 2004;PEREIRA et al, 2010;FIORIO et al, 2017).…”
Section: Discussionmentioning
confidence: 85%
“…There is still no consensus on the antiinflammatory activity of PBMT because previous studies have indicated a possible anti-inflammatory activity at the initial stages of the wound-healing process (MEDRADO et al, 2008;VILELA et al, 2012;, whereas other authors did not detect this activity (VIEGAS et al, 2007). There is also the report of the modulation of inflammatory mediators (FIORIO et al, 2017). Our results indicate that the absolute number of leukocytes and the score of the semi-quantitative histopathological evaluation (i.e., polymorphonuclear infiltration) were lower in the TG than in the CG; however, these differences were not significant and consequently did not confirm the anti-inflammatory activity of GaAs PBMT.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The effect of PBM in aged animals has also been shown to be effective. Fiorio et al [44] investigated PBMT (660 nm, 1.07 W/cm 2 , 72 J/cm 2 ) in cutaneous wound healing in aged rats (500 days). The study demonstrated that PBM is effective in the modulation of inflammatory mediators (IL-6, CINC-1, and VEGF) and matrix metalloproteinases and their inhibitors (MMP-3, MMP-9, and TIMP-2).…”
Section: Cellular Effects Of Pbmmentioning
confidence: 99%
“…Em pele, alguns artigos na literatura também reportam que a PBMT apresentou efeitos positivos na modulação do processo inflamatório e estimulação da proliferação celular (como células precursoras miogênicas e fibroblastos), podendo, dessa maneira, resultar em uma maior produção de colágeno, e consequentemente em uma cicatrização melhorada do tecido (118,135,166).…”
Section: Introductionunclassified